2006
DOI: 10.1016/j.febslet.2006.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic effect of vascular endothelial growth factor during germ layer formation of human embryonic stem cells

Abstract: Vascular endothelial growth factor (VEGF), a potent mitogen for vascular endothelial cells, has been suggested as a modulator that is involved in neurogenesis as well as angiogenesis. Here, we directly examined the effect of VEGF on neuroectodermal differentiation using human embryonic stem cells (hESCs). VEGF treatment upregulated the expression of neuroectodermal genes (Sox1 and Nestin) during germ layer formation in embryoid bodies (EBs) and efficiently increased the number of neural rosettes expressing bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…These revealed that in the differentiation of hESCs, VEGF could promote neural stem cell proliferation. The study from Kim [20] reported that VEGF could up-regulate the expression of neuroectodermal Sox1 and Nestin gene, which were consistent with the findings in this study. Our study further confirmed that VEGF inhibited neural stem cells differentiated into glial cells, and illustrated indirectly those neural stem cells treated with VEGF had greater potential to differentiate into neurons (the data that VEGF directly promotes neuron proliferation were not shown).…”
Section: Discussionsupporting
confidence: 94%
“…These revealed that in the differentiation of hESCs, VEGF could promote neural stem cell proliferation. The study from Kim [20] reported that VEGF could up-regulate the expression of neuroectodermal Sox1 and Nestin gene, which were consistent with the findings in this study. Our study further confirmed that VEGF inhibited neural stem cells differentiated into glial cells, and illustrated indirectly those neural stem cells treated with VEGF had greater potential to differentiate into neurons (the data that VEGF directly promotes neuron proliferation were not shown).…”
Section: Discussionsupporting
confidence: 94%
“…Neurotrophins such as brain-derived neurotrophic factor and growth factors such as vascular endothelial growth factor and fibroblast growth factor 2 are released from endothelial cells [31,32] and influence neuronal survival, proliferation and differentiation [33]. Thus, an increased release of these growth factors, due to an increase in angiogenesis, may contribute to the foetal neurogenic niche and mediate the proliferative effect; this warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A stimulates dopaminergic neuron development in vitro in prenatal rat mesencephalic explants (Silverman et al, 1999). VEGF-A application during the formation of embryoid bodies from human embryonic stem cells promotes the generation of neuroectodermal cells, which are differentiating mainly into neurons retaining a dopaminergic phenotype (Kim et al, 2006). Mice lacking hypoxia-inducible factor-1, which have lower VEGF-A levels in the brain, develop fewer dopaminergic neurons (Milosevic et al, 2007).…”
Section: Flt-1tkmentioning
confidence: 99%